Advances in platinum-based cancer therapy: overcoming platinum resistance through rational combinatorial strategies - Yusoh, Nur Aininie; Ahmad, Haslina; Vallis, Katherine A.; Gill, Martin R. (Springer, 2025)
Platinum-based cancer therapy remains a cornerstone of first-line treatment for several solid tumours such as ovarian, testicular, and non-small cell lung cancers, where it has received regulatory approval as both monotherapy and combination regimens. However, the inevitable emergence of resistance has necessitated extensive preclinical and clinical efforts to develop rational platinum-based combinations. The most appealing candidates for combination therapy are those that offer additive and/or synergistic effects without undesirable overlapping toxicities. Whilst early strategies focussed on co-administration with cytotoxic chemotherapies, recent advances have shifted towards combinations with targeted therapies and immunotherapies, offering improved efficacy and durability of response. In this review, we provide a comprehensive analysis of recent clinical trials evaluating platinum-based combination strategies (excluding radiotherapy) and give an overview of trial concepts that will lead to more refined therapies for cancer. We also highlight emerging dual-drug codelivery nanosystems, platinum-based antibody–drug conjugates (ADCs), and multi-targeted platinum compounds with promising preclinical and/or clinical evidence. Beyond traditional drug pairings, the improved design strategies of new platinum compounds such as their incorporation into ADCs offer enhanced targeting and reactivity. Whilst promising preclinical examples like trastuzumab-Pt(II) and cetuximab-C8Pt(IV) bring optimism to combinatorial approaches, significant challenges including stability and controlled payload release remain to be addressed before clinical translation. By integrating advances in molecular profiling and rational drug development, platinum-based therapies continue to evolve, offering renewed optimism for overcoming drug resistance and improving patient outcomes, although challenges such as biomarker identification, toxicity management, and treatment costs remain to be fully addressed.